2012
DOI: 10.1186/1471-2172-13-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-related accumulation of T cells with markers of relatively stronger autoreactivity leads to functional erosion of T cells

Abstract: BackgroundThymic involution is a prominent characteristic of an aging immune system. When thymic function is reduced/absent, the peripheral T cell pool is subject to the laws of peripheral T cell homeostasis that favor survival/expansion of T cell receptors with relatively higher functional avidity for self-peptide/MHC complexes. Due to difficulties in assessing the TCR avidity in polyclonal population of T cells, it is currently not known whether high avidity T cells preferentially survive in aging individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…The analyses of CD4+ TCRαβ + lymphocyte profile in age-matched rats immunized with CFA only showed that this difference was specific to immunization with specific (auto)antigens. This was consistent with data indicating the accumulation of T cells with autoreactive specificities with aging in both humans and experimental animals [ 20 , 64 ]. This phenomenon has been related to the erosion of naïve T cell pool with aging, and consequent residual T-cell proliferation to reconstitute their nearly normal numbers [ 65 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The analyses of CD4+ TCRαβ + lymphocyte profile in age-matched rats immunized with CFA only showed that this difference was specific to immunization with specific (auto)antigens. This was consistent with data indicating the accumulation of T cells with autoreactive specificities with aging in both humans and experimental animals [ 20 , 64 ]. This phenomenon has been related to the erosion of naïve T cell pool with aging, and consequent residual T-cell proliferation to reconstitute their nearly normal numbers [ 65 ].…”
Section: Discussionsupporting
confidence: 93%
“…This phenomenon has been related to the erosion of naïve T cell pool with aging, and consequent residual T-cell proliferation to reconstitute their nearly normal numbers [ 65 ]. In this compensatory event T cells with higher avidity for self-peptide/MHC complexes enjoy advantage and expand more relative to the low avidity T cells [ 20 ]. This leads to the accumulation of high avidity T cells, which is potentially dangerous due to increased risk of autoimmune disorders [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of population aging due to increasing life expectancy cannot be excluded. Moreover, significant increases in MG incidence rates in the elderly could be partially explained by increased susceptibility to autoimmune diseases in older persons due to aging of the immune system [21] or the influence of certain environmental factors. …”
Section: Discussionmentioning
confidence: 99%
“…38 Premature aging of the immune system and incidence of cytomegalovirus (CMV) infection were sequelae of thymectomy during infancy 39 In reduced or absent thymic function and aged immune system, the peripheral T cell population becomes regulated through the persistence and expansion of the T cell receptors together with their increased functional greediness for own peptides. 40 Progressive decline in immunity with aging results in increased incidence of infections and impaired responses to vaccines. 41 With the sixth decade of life, the human immune system begins profound aging-related changes which ultimately ends in a state of immunosenescence.…”
Section: Aging and Immune Systemmentioning
confidence: 99%